Inactivation of CYP3A4 by Benzbromarone in Human Liver Microsomes - Masubuchi, Yasuhiro; Kondo, Shinji (Drug Metabolism Letters, 2016)
Background: Benzbromarone is a uricosuric drug in current clinical use that can cause serious hepatotoxicity. Chemically reactive and/or cytotoxic metabolites of benzbromarone have been identified; however there is a lack of available information on their role in benzbromarone hepatotoxicity. The reactive metabolites of some hepatotoxic drugs are known to covalently bind, or alternatively are targeted, to specific cytochrome P450 (P450) enzymes, a process that is often described as mechanism-based inhibition. Objective: We examined whether benzbromarone causes a mechanism-based inhibition of human P450 enzymes. Method: Microsomes from human livers were preincubated with benzbromarone and NADPH, followed by evaluation of CYP2C9 and CYP3A4 activities. Results: Benzbromarone metabolism resulted in inhibition of CYP3A4 but not CYP2C9 in a time-dependent manner. Confirmation of pseudo-first order kinetics of inhibition, a requirement for NADPH, and a lack of protection by scavengers suggested that benzbromarone is a mechanism-based CYP3A4 inhibitor. Conclusion: Modification of the P450 enzyme by the reactive metabolite is a common trait of drugs that induce idiosyncratic hepatotoxicity, and might provide a speculative, mechanistic model for the rare occurrences of this type of drug toxicity.
Keywords: Benzbromarone